The Role of Digital Archival Governance: Public Service Innovation Based on Smart City - Baharuddin, Aris; Munna, Afzal Sayed; Abdullah, Asmilah; Asmar; Salam, Rudi (Program Studi Ilmu Perpustakaan UIN Alauddin, 2025)
This study explores the influence of digital archival governance on service efficiency, transparency, and accessibility in Makassar City. The data were gathered through semi-structured interviews, observations, and document analysis involving government officials, policymakers, and IT personnel. The findings indicated that the effectiveness of digital archival governance was shaped by institutional preparedness, supportive legal frameworks, community engagement, and technological infrastructure. Capacity-building programs and professional training were essential to enhance the digital competencies of public servants, while participatory governance mechanisms contributed to greater public trust and access. Additionally, emerging technologies such as blockchain and artificial intelligence presented significant opportunities for optimizing archival systems, though they also introduce challenges related to cybersecurity and ethical management. This study contributes to the discourse on smart governance by highlighting both best practices and obstacles encountered in implementing digital transformation within public administration. It concludes by emphasizing the importance of collaborative governance models, adaptive institutional strategies, and ongoing technological innovation to ensure inclusive and sustainable urban development. Makassar’s experience offers valuable insights for other cities aiming to strengthen digital archival governance as a foundation for improved public service delivery.